Gestión administrativa del Almacén Jarrin Herrera ubicado en el cantón Babahoyo, período 2024. - Márquez Parrales, Jonathan Ariel (2025)
The objective of this case study is to analyze the administrative management of the Jarrín Herrera Warehouse in Babahoyo during the year 2024, the purpose of which is focused on identifying deficiencies in the administrative procedures implemented and proposing improvement strategies. To achieve this investigative objectivity, a qualitative-quantitative approach based on an analytical method was used, which achieved a comprehensive assessment of each of the factors that influence the operational efficiency of the business. It should be noted that surveys were carried out aimed at the company's staff and an interview with the manager, with the purpose of understanding the perception of human talent about the administrative, logistical and technological processes that have been implemented. The results showed that, although the warehouse maintains established and ambiguous procedures, these have structural flaws that affected operational efficiency. Likewise, a level of dissatisfaction on the part of employees was detected, derived from the absence of training on issues of the use and management of digital tools, as well as problems based on inventory management, product distribution and assignment of functions. In conclusion, the continuous improvement of strategies focused on the optimization of administrative processes, the implementation of new technologies and the appropriate assignment of functions to human talent is recommended, which will allow optimization of productivity and competitiveness by the warehouse within the commercial center of Babahoyo.